1145. The Role of the Plasmid-Mediated Fluoroquinolone-Resistance (PMFQR) Genes As Resistance Mechanisms in Pediatric Infections due to Enterobacterales (Ent). (4th December 2021) - Pitstick, Claire E; Marshall, Steven; Konda, Sreenivas; Medernach, Rachel L; Domitrovic, T Nicholas; Hujer, Andrea M; Qureshi, Nadia K; Rudin, Susan D; Zheng, Xiaotian; Weinstein, Robert A; Bonomo, Robert A; Logan, Latania K
Abstract: Background: Fluoroquinolones (FQs) are not commonly prescribed in children, yet the increasing incidence of multidrug resistant (MDR) Ent infections in this population often reveals FQ resistance. We sought to define the role of FQ resistance in the epidemiology of MDR Ent in children, with an overall goal to devise treatment and prevention strategies. Methods: A case-control study of children (0-18 years) at 3 Chicago hospitals was performed. Cases had infections by FQ susceptible, 3 rd generation cephalosporin-resistant (3GCR) and/or carbapenem-resistant (CR) Ent harboring a non or low level expressed PMFQR gene (PMFQS Ent). Controls had FQR infections due to 3GCR and/or CR Ent with expressed PMFQR genes (PMFQR Ent). We sought bla genes by PCR or DNA (BD Max Check-Points assay®) and PMFQR genes by PCR. We performed Rep-PCR, MLST, and E. coli phylogenetic grouping. Demographics; comorbidities; and device, antibiotic, and healthcare exposures were evaluated. Predictors of infection were assessed. Results: Of 170 G3CR and/or CR Ent isolates, 85 (50%) were FQS; 23 (27%) had PMFQR genes (PMFQS cases). 85 (50%) were FQR; 53 (62%) had PMFQR genes (PMFQR controls). The median age for children with PMFQS Ent and PMFQR Ent were 4.3 and 6.2 years, respectively (p=NS). Of 23 PMFQS Ent, 53% were Klebsiella and of 53 PMFQR Ent, 76% were E. coli . The most common bla and PMFQR genes in PMFQS Ent were bla SHV ESBL (44%); oqxB (57%) and aac-6'1b-cr (52%) and in PMFQR Ent were bla CTX-M-1 group (76%); aac-6'1b-cr (91%) and oqxA (17%). Multivariable regression analysis showed children with PMFQS Ent infections were more likely to have hospital onset infection (OR 5.7, 95% CI 1.6-22) and isolates with multiple bla genes (OR 3.8, 95% CI 1.1-14.5). The presence of invasive devices mediated the effects of healthcare setting in the final model. Differences in demographics, comorbidities, or antibiotic use were not found. Conclusion: Paradoxically, PMFQS Ent infections were often hospital onset and PMFQR Ent infections were community onset. PMFQS Ent commonly co-harbored multiple bla and PMFQR genes, affecting therapeutic options and suggesting need for contact precautions. Control of PMFQS Ent infections in children will require validating sources and risk factors. Disclosures: Robert A. Bonomo, MD, entasis (Research Grant or Support)Merck (Grant/Research Support)NIH (Grant/Research Support)VA Merit Award (Grant/Research Support)VenatoRx (Grant/Research Support)